2020
DOI: 10.1017/ice.2020.234
|View full text |Cite
|
Sign up to set email alerts
|

Prospective monitoring of carbapenem use and pseudomonal resistance across pediatric institutions

Abstract: Objective: To determine whether carbapenem consumption and Pseudomonas aeruginosa resistance rates can be used as benchmarks to compare and improve antimicrobial stewardship programs across multiple pediatric hospitals. Design: A prospective study. Setting and participants: Healthcare institutions in Japan with >100 pediatric beds. Methods: An annual survey of the total days of therapy (DOT) per 1,000 patient days for carbapenem antibiotics (meropen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 15 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…In pediatric settings, an improvement in susceptibility to meropenem in P. aeruginosa was observed from a median of 87% to 89.7% over the 7 year period. 33 Our study did not report the drug susceptibility pattern in our setting, and further reports are needed about this. This study was the first prospective study of acceptance rate and clinical outcomes of meropenem de-escalation in pediatric patients in Thailand.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In pediatric settings, an improvement in susceptibility to meropenem in P. aeruginosa was observed from a median of 87% to 89.7% over the 7 year period. 33 Our study did not report the drug susceptibility pattern in our setting, and further reports are needed about this. This study was the first prospective study of acceptance rate and clinical outcomes of meropenem de-escalation in pediatric patients in Thailand.…”
Section: Discussionmentioning
confidence: 76%
“…© 2021 Japan Pediatric Society Meropenem deescalation in pediatrics 1463 de-escalation, which resulted in the lower consumption of meropenem, can reduce the incidence of CR-GNB. There were studies in Japan 21,33 that reported the inverse correlation of carbapenem consumption and susceptibility of carbapenems in P. aeruginosa. In pediatric settings, an improvement in susceptibility to meropenem in P. aeruginosa was observed from a median of 87% to 89.7% over the 7 year period.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of carbapenem-resistant Gram-negative bacteria (GNB) with the consequent change in institutional epidemiology continues to evolve rapidly worldwide [ 13 ]. Previous studies have showed that carbapenem resistance in GNB appeared to correlate with previous exposure to carbapenems [ 14 17 ] while reduction of carbapenem use, the incidence of Clostridioides difficile infection decreased [ 18 ]. Improper carbapenems use in targeted therapy for IPD should be reduced in China.…”
Section: Discussionmentioning
confidence: 99%
“…The spread of carbapenem-resistant Gramnegative bacteria (GNB) with the consequent change in institutional epidemiology continues to evolve rapidly worldwide [12]. Previous studies have showed that carbapenem resistance in GNB appeared to correlate with previous exposure to carbapenems [13,14,15,16]. And with reduction in carbapenem use, the incidence of Clostridioides di cile infection decreased [17].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inappropriate antibiotics therapy group of meningitis also had higher proportion of patients with ICU admission, tracheal intubation and death (all P values 0.001), compared with appropriate antibiotics therapy group of meningitis (Table 5). 16.9% in the south, 12.5% in the northwest) and linezolid (11.1% in the north, 7.2% in the south, 1.9% in the east, 2.5% in the northwest) all differed by region (all P values 0.02) (Table 6). Inappropriate use rate of carbapenems and vancomycin was highest in the east.…”
Section: Demographic Datamentioning
confidence: 95%